Effect of Training, Career Development, And Compensation On Employee Performance at PT Bank Mandiri (Persero) Tbk - Fitriani, Dewi; Hazizan, Halipi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
One sort of quantitative research is used in this investigation. The dependent variables in this causality study design include training, career advancement, and compensation, whereas the independent variable is employee performance. This research was conducted at Bank Mandiri Cikarang Jababeka which is located in the Cikarang Industrial area, Indonesia. The individuals that work at Bank Mandiri Cikarang Jababeka Ruko Roxy comprise the population under investigation. In this survey, 27 employees made up the population. Non-probability sampling is the method of sampling used in this investigation. Bank Mandiri Cikarang Jababeka uses questionnaires to collect information from respondents on their training, professional growth, and pay. SPSS software was used to aid with data processing for this investigation. This study employs a number of data analysis techniques, such as validity tests, reliability tests, multiple linear regression analysis tests that comprise hypothesis testing (F, T, and Determination tests), and classical assumption tests (normality, heteroscedasticity, and multicollinearity tests). The results of this study state that There is a positive and significant partial effect of the training variable (X1) on performance (Y), There is a positive and partially significant effect of the career development variable (X2) on employee performance (Y), There is a positive and significant partial effect of the compensation variable (X3) on performance (Y), Training, career development, and compensation together or simultaneously have a positive and significant effect on employee performance, The correlation or relationship between training, career development, and compensation on employee performance at Bank Mandiri Cikarang Jababeka is quite strong at (r = 0.541) and the coefficient of determination or r square number is 0.598% or equal to 59.8%.